(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2022)
Background: The ongoing pandemic has caused severe crisis in the hospitality sector with millions of people forced to stay home and under quarantine to stop the spread of contagion. The following paper aims to highlight the problems and difficulties faced by the hospitality sector and the host communities in particular due to the mandatory nation-wide lockdown owing to COVID-19 pandemic. Objective: The purpose of the study was to analyse and highlight the common characteristics of the host community towards the stranded international and domestic travellers while catering and accommodating them owing to local authorities’ obligatory lockdown along with the forced shutdown of hotels and large commercial establishments in Rohtak and Durgapur. Methodology: The geographical area of the research and data collection was limited to the city of Rohtak in Haryana and Durgapur in the state of West Bengal. Population of the study is limited to the region of Rohtak and Durgapur. The number of participants or respondents were 42.The paper is exploratory in design and follows a qualitative methodological approach. The data was collected with the help of an online self-report questionnaire. Results: Over a period of 95 days, the interviews of hosts and tourists were conducted. The content analysis revealed eight themes in all the recorded interviews. A majority of tourists and host communities were impacted by the pandemic in psychological aspects by 35.7%, followed by accommodation and protocols by 33.3% each. Conclusion: There have been various studies that have been conducted in the backdrop of COVID-19 pandemic but not many of them have highlighted the importance of host communities which are an indispensable part of our society as well as the hospitality sector.